Should renewable energy policy be 'renewable'?. (23rd April 2019) - Gawel, Erik; Lehmann, Paul
Abstract: Political flexibility brings about trade-offs for policy-makers aiming to support the deployment of renewable energy sources (RES). On the one hand, it allows incorporating new information on ex ante uncertain benefits and costs of RES policy. On the other hand, it may deter RES investments. This paper scrutinizes how these trade-offs play out economically and politically when RES policy-makers choose the degree of flexibility as well as the instruments to implement flexibility. The analysis builds on a theoretical framework distinguishing between flexibility by design and by adjustment. It is complemented by a discussion of three case studies: RES support schemes in Germany and the United Kingdom, and the EU Emissions Trading Scheme. Theoretical as well as empirical results suggest that the politically chosen degree of flexibility by policy design may be sub-optimally low. In contrast, flexibility by policy adjustment is often excessively high.